Phenological variability drives the distribution of wildfires in Sardinia - Angelis, Antonella; Bajocco, Sofia; Ricotta, Carlo (Landscape Ecology, 2012)
Fuel characteristics play an important role in driving ﬁre ignition and propagation; at the landscape scale fuel availability and ﬂammability are closely related to vegetation phenology. In this view, the NDVI proﬁles obtained from high temporal resolution satellites, like MODIS, are an effective tool for monitoring the coarse-scale vegetation seasonal timing. The aim of this paper is twofold: our ﬁrst objective consists in classifying by means of multitemporal NDVI proﬁles the coarse-scale vegetation of Sardinia into ‘phenological clusters’ in which ﬁre incidence is higher (preferred) or lower (avoided) than expected from a random null model. If ﬁres would burn unselectively, then ﬁres would occur randomly across the landscape such that the number of ﬁres in a given phenological cluster would be nearly proportional to the relative area of that land cover type in the analyzed landscape. Actually, certain vegetation types are more ﬁre-prone than others. That is, they are burnt more frequently than others. In this framework, our second objective consists in investigating the temporal parameters of the remotely sensed NDVI proﬁles that best characterize the observed phenology–ﬁre selectivity relationship. The results obtained show a good association between the NDVI temporal proﬁles and the spatio-temporal wildﬁre distribution in Sardinia, emphasizing the role of bioclimatic timing in driving ﬁre regime characteristics.
Keywords: Clustering; Fire selectivity; Image segmentation; MODIS; NDVI proﬁles; Residuals

Evidence of selective burning in Sardinia (Italy): which land-cover classes do wildfires prefer? - Bajocco, Sofia; Ricotta, Carlo (Landscape Ecology, 2007)
The objective of this paper is to identify land-cover types where ﬁre incidence is higher (preferred) or lower (avoided) than expected from a random null model. Fire selectivity may be characterized by the number of ﬁres expected in a given land-cover class and by the mean surface area each ﬁre will burn. These two components of ﬁre pattern are usually independent of each other. For instance, ﬁre number is usually connected with socioeconomic causes whereas ﬁre size is largely controlled by fuel continuity. Therefore, on the basis of available ﬁre history data for Sardinia (Italy) for the period 2000– 2004 we analyzed ﬁre selectivity of given land-cover classes keeping both variables separate from each other. The results obtained from analysis of 13,377 ﬁres show that for most land-cover classes ﬁre behaves selectively, with marked preference (or avoidance) in terms of both ﬁre number and ﬁre size. Fire number is higher than expected by chance alone in urban and agricultural areas. In contrast, in forests, grasslands, and shrublands, ﬁre number is lower than expected. In grasslands and shrublands mean ﬁre size is signiﬁcantly larger than expected from a random null model whereas in urban areas, permanent crops, and heterogeneous agricultural areas there is significant resistance to ﬁre spread. Finally, as concerns mean ﬁre size, in our study area forests and arable land burn in proportion to their availability without any signiﬁcant tendency toward ﬁre preference or avoidance. The results obtained in this study contribute to ﬁre risk assessment on the landscape scale, indicating that risk of wildﬁre is closely related to land cover.
Keywords: analysis á; Fire number; fire number á fire; Fire selectivity; Fuel fragmentation; fuel fragmentation á landscape; Landscape analysis; mean fire size á; Mean ﬁre size; Permutation methods; selectivity á

Evidence of selective burning in Sardinia (Italy): which land-cover classes do wildfires prefer? - Bajocco, Sofia; Ricotta, Carlo (Landscape Ecology, 2007)
The objective of this paper is to identify land-cover types where ﬁre incidence is higher (preferred) or lower (avoided) than expected from a random null model. Fire selectivity may be characterized by the number of ﬁres expected in a given land-cover class and by the mean surface area each ﬁre will burn. These two components of ﬁre pattern are usually independent of each other. For instance, ﬁre number is usually connected with socioeconomic causes whereas ﬁre size is largely controlled by fuel continuity. Therefore, on the basis of available ﬁre history data for Sardinia (Italy) for the period 2000– 2004 we analyzed ﬁre selectivity of given land-cover classes keeping both variables separate from each other. The results obtained from analysis of 13,377 ﬁres show that for most land-cover classes ﬁre behaves selectively, with marked preference (or avoidance) in terms of both ﬁre number and ﬁre size. Fire number is higher than expected by chance alone in urban and agricultural areas. In contrast, in forests, grasslands, and shrublands, ﬁre number is lower than expected. In grasslands and shrublands mean ﬁre size is signiﬁcantly larger than expected from a random null model whereas in urban areas, permanent crops, and heterogeneous agricultural areas there is significant resistance to ﬁre spread. Finally, as concerns mean ﬁre size, in our study area forests and arable land burn in proportion to their availability without any signiﬁcant tendency toward ﬁre preference or avoidance. The results obtained in this study contribute to ﬁre risk assessment on the landscape scale, indicating that risk of wildﬁre is closely related to land cover.
Keywords: analysis á; Fire number; fire number á fire; Fire selectivity; Fuel fragmentation; fuel fragmentation á landscape; Landscape analysis; mean fire size á; Mean ﬁre size; Permutation methods; selectivity á